Risk Factors of Low Birth Weight (LBW) among Infants at dr. R. Soedjono General Hospital East Lombok - Yuliani; I Wayan Gede Artawan Eka Putra; I Gusti Ayu Trisna Windiani (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: The infant mortality rate related to low birth weight (LBW) in the East Lombok district increased from 18.0% in 2012 to 26.1% in 2013. This study aimed to identify the risk factors of LBW among infants in dr. R. Soedjono General Hospital, East Lombok. Methods: A case-control study was conducted in dr. R. Soedjono General Hospital involving 59 LBW and 118 normal weight infants as controls (1:2) which were selected by systematic random sampling. Secondary data regarding chronic energy deficiency and anemia were collected using medical records and delivery register. Data on maternal characteristics,birth spacing, access to antenatal care,  socioeconomic status, cigarette smoke exposure, wood smoke exposure and mosquito repellent exposure were collected through interviews. Data were analyzed using bivariate to determine crude OR and multivariate to calculate adjusted OR. Results: Characteristics of cases and controls was similar in terms of education, employment and maternal parity, but significantly different in age. Multivariate analysis showed that variables significantly associated with LBW were income with OR=2.3 (95%CI: 1.06-4.9), cigarette smoke exposure with OR=2.9 (95%CI: 1.31- 6.33), chronic energy deficiency with OR=3.1 (95%CI: 1.24-7.59) and maternal ages <20 years or >35 years with OR=3.2 (95%CI: 1.46-6.90). Wood smoke exposure and anemia were not significantly associated with LBW with OR=1.2 (95%CI: 0.44-2.88) and OR=1.1 (95%CI: 0.82-1.27). Conclusion: Risk factors associated with LBW among infants were low income, cigarette smoke exposure, chronic energy deficiency and mother’s age <20 years or >35 years.